PENERAPAN ALGORITMA FIRST FIT UNTUK MEMANAJEMEN PENDISTRIBUSIAN BANTUAN LOGISTIK BENCANA BERBASIS WEB PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN PONOROGO - Yusika Destiana; Dwiyono Ariyadi; Indah Puji Astuti (Universitas Muhammadiyah Ponorogo, 2021)
In dealing with disasters, the government has a regional institution in charge of disaster management which includes prevention, handling, rehabilitation, reconstruction in a fair and equal manner, namely the Regional Disaster Management Agency. With disaster management efforts, there will be irregularities in the logistics management of aid that will be distributed to residents because the distribution of aid is carried out by various parties. Based on the above problems, it is necessary to have a management system for the distribution of aid that can adjust according to priority needs evenly. In this study, the First Fit algorithm method was used to build a website-based natural disaster aid distribution information system.